2018
DOI: 10.14814/phy2.13784
|View full text |Cite
|
Sign up to set email alerts
|

Differential electrophysiological properties of D1 and D2 spiny projection neurons in the mouse nucleus accumbens core

Abstract: The striatum consists of the dorsal (caudate/putamen) and the ventral (nucleus accumbens) regions. The nucleus accumbens is further divided into a core and shell. Both the dorsal and ventral striatum contain populations of spiny projection neurons, which make up 95% of the neurons within the striatum. SPNs are canonically categorized into those that express the D1‐type dopamine receptor (D1 SPNs) and those that express the D2‐type dopamine receptor (D2 SPNs). D1 and D2 SPNs differ with respect to both synaptic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 32 publications
3
27
0
Order By: Relevance
“…To determine whether the alterations in inhibitory transmission are due to action potential dependent or independent release of neurotransmitter we also assed tetrodotoxin -insensitive mIPSCs (TTX, voltage-gated sodium channel blocker). mIPSC frequency was increased in D1 SPNs of MMP-1OE (0.95 ± 0.13 Hz) mice in comparison those from either control 29 (0.39 ± 0.08 Hz, p = 0.0102) or MMP-1OE/PAR-1KO mice (0.39 ± 0.07 Hz, p = 0.0067, Fig. 1b,g ).…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…To determine whether the alterations in inhibitory transmission are due to action potential dependent or independent release of neurotransmitter we also assed tetrodotoxin -insensitive mIPSCs (TTX, voltage-gated sodium channel blocker). mIPSC frequency was increased in D1 SPNs of MMP-1OE (0.95 ± 0.13 Hz) mice in comparison those from either control 29 (0.39 ± 0.08 Hz, p = 0.0102) or MMP-1OE/PAR-1KO mice (0.39 ± 0.07 Hz, p = 0.0067, Fig. 1b,g ).…”
Section: Resultsmentioning
confidence: 84%
“…sIPSC frequency was significantly increased in D1 SPNs from MMP-1OE mice (1.4 ± 0.16 Hz) in comparison to those from either control 29 (0.71 ± 0.14 Hz, p = 0.0165) or MMP-1OE/PAR-1KO mice (0.74 ± 0.13 Hz, p = 0.0219, Fig. 1a,c ).…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Several reports have shown that changes in neuronal excitability correlate with remodeling of their dendritic arbors (Al-Muhtasib et al, 2018;Cazorla et al, 2012;Fieblinger et al, 2018). We assessed this with Sholl analysis of three dimensional neuritic arbor reconstructions from streptavidin labeled ChIs that were filled with biotin during recording ( Figure 3A).…”
Section: Electrophysiological Characteristics and Synaptic Input To Smentioning
confidence: 99%